Nutritional Requirements of Azadirachta Excelsa (Jack) Jacobs Stand at Labis, Johore - Ong, Kian Huat (2004)
The growth of forest is a long-term process. Studying the cycling of nutrients is important in order to understand the ecological functioning of a forest. The use of fertilizers in forest management has a profound effect on nutrient cycling processes at the plant-soil interphase. The transfer of nutrients among the various compartments or pools is a continuous process and the aim of the present study is to quantify the flow of nutrients between these pools and to identify some of the factors involved in influencing this process. A field experiment in Sungai Karas, Johore, Malaysia was initiated with the objective of evaluating growth responses and distribution of nutrients within tree compartments in Azadirachta excelsa (Jack) Jacobs under different fertilizer regimes. The findings should provide plantation managers with some baseline data on nutrition management in A. excelsa plantations. The treatments involved a factorial combination of three rates of urea N (50, 100 and 150 kg ha-1), three rates of triple superphosphate P (50, 75 and 100 kg ha-1) and two rates of dolomite lime (0 or 53.25 kg Ca and 30 kg Mg ha-1) applied in split (three times; 26, 30, and 34 months after planting) in a 2-year-old stand established on a degraded soil. Slope, in association with soil depth, had the greatest influence on stand growth two years after planting. The growth parameters were negatively correlated with slope and soil exchangeable K. Soil nutrient status remained unchanged despite receiving regular fertilizer application, suggesting that higher requirement and uptake by the plants or leaching had taken place. Thus, proper site selection and fertilizer application rate are important factors to be considered when establishing A. excelsa stands. Thirty-six trees were randomly selected from different treatments and harvested for biomass assessment. Based on the harvested samples, the effect of fertilizers and dolomite lime were insignificant on biomass production. This may be caused by competition from the undergrowth and low levels of fertilizer used. The aboveground biomass ranged from 3.4 to 28.4 t ha-1, of which 6.6% was foliage. Equations for predicting stem volume were also developed in the present study using the data from felled trees. The equations were selected from three commonly used models and validated using data from 36 tree samples from the 4-year-old plantation. The least biased and most precise estimates of stem volume were obtained using the logarithmic equation. Regression equation using diameter at breast height as the variable was a good predictor of aboveground biomass among the prediction variables tried. Concentrations of nutrient were highest in foliage with the exception of Ca. The total nutrient contents in the aboveground biomass (in kg ha-1) were 45.15 for N, 6.66 for P, 39.67 for K, 5.97 for Mg and 11.43 for Ca. Current harvesting method of timber coupled with burning activity during site preparation would result in the removal of substantial amounts of nutrients, and may lead to degradation of site quality. Mean increments of tree volumes (estimated using regression) in two years of observation or 51 months after planting ranged from 25.95 to 54.67 m3 ha-1. Growth of A. excelsa was strongly influenced by the addition of N. Foliar P concentration was increased by additions of N and P at 39 months but this was not found at 51 months. Consequently strong correlation between P foliar nutrient concentrations and growth was found at 39 months. The best growth was associated with foliar concentrations at 39 months of about 2.57% N and 0.27% P. The rather substantial decrease in growth in second half of the experiment indicates the need to continually repeat fertilizer application to sustain growth rates. Additions of dolomite lime and fertilizers increased soil pH, and concentrations of Mg and Ca in the soil two years after the commencement of the present study. Liming led to a reduction of soil total N suggesting higher N mineralization may have taken place. Application of N and P increased soil total N and P availability in the soil. Mean annual litterfall ranged from 4.95 to 6.60 t ha-1 yr-1. The addition of fertilizer and dolomite lime did not result in any changes in the mass of litterfall. Leaf litter accounted for more than 88% of total litter production. The mean standing crop of leaf litter ranged from 1.26 to 3.76 t ha-1. Nitrogen application increased the mass of leaf litter accumulated on the forest floor but not the nutrient concentration of the leaf litter. Differences among the treatments were found only at the early stages of decomposition for both the decomposition rates and weight losses. Release of the nutrients at the end of the experiment was positively correlated with their initial concentration. The results highlight the importance of understanding nutrient fluxes before recommending a fertilization regime aimed at increasing productivity of A. excelsa plantations. General fertilizer prescriptions and management practices of A. excelsa plantation are presented. However, detailed assessments of fertilizer requirements are required if soil types other than those described here are used.